Ranking of commercial loan evaluation criteria and risk ratio in practice by domestic commercial banks and financial institution: a study in Kuala Terengganu / Azli Nizam Md Guzali, Syed Hussain Tuan Embong and Hashim Jusoh - Md Guzali, Azli Nizam; Tuan Embong, Syed Hussain; Jusoh, Hashim (2007)
This study attempts to assess and rank credit criteria applicable in evaluating credit application by commercial banks using the best practice model. This research would improve evaluation processes for credit managers in comparison to the best practices by credit managers, customer knowledge can be enhanced to improve requirements and information on loan application for the credit facilities, and by using various statistical tools such as mean, standard deviation, coefficient of variation, coefficient of determination and Chi- square tests, the best practices model can be adopted and applied in the loan evaluation process for multi-criteria decision making in commercial banking sector.